Sourcing ideas for textile design researching colour, surface, structure, texture and pattern - Steed, Josephine; Stevenson, Frances (Basics textile design, 2020)
"Introduces research and ideas-gathering techniques to help readers produce original textile designs."--Provided by publisher.